The Use of Artificial Intelligence for Sustainable Local Governments in Nepal: A Framework for Digitalization of Public Service Delivery - Subedi, Prakash (Academia Journal of Humanities & Social Sciences, 2026)
Artificial intelligence (AI) is increasingly discussed as a transformative tool for improving efficiency, transparency, and responsiveness in the public service delivery. In Nepal’s federal governance system, the local governments are expected to deliver a wide range of services with the limited institutional and human capacity, making the public service delivery effective. This study examines the preparedness of Pokhara Metropolitan City to adopt AI-based tools, focusing on Wards 26 and 27 as the representative units of the frontline service delivery. A mixed-method research design was employed, combining a structured survey of 32 ward-level officials and staff with the document analysis of municipal policies and digital governance initiatives. The findings indicate that the basic digital infrastructure, such as the internet connectivity and device availability, is largely in place. The leadership support for the digital innovation and positive perceptions of AI benefits are also strong. However, the institutional readiness remains moderate due to some gaps in the policy frameworks, fragmented digital systems, and limited strategic planning for an AI adoption. Human capacity emerges as the most significant constraint with an inadequate training and limited exposure to the advanced digital tools despite a high willingness to learn. Based on these findings, the paper proposes a phased strategic framework emphasizing the infrastructure integration, AI governance, and capacity building. The study develops an empirical evidence to apply this framework in the ward-level context and offers a practical guidance for sustainable AI adoption in Nepali local governments.